Signaling the importance of training. Issue 7 (2nd September 2014) - Towler, Annette; Watson, Aaron; A. Surface, Eric
Abstract : Purpose: – In this study of 815 military personnel, the purpose of this paper is to examine how perceived leader behaviors are related to trainee perceptions of leader training priorities and to trainee priority for training, and whether trainee motivation to transfer of training moderated the relationship between trainee perceptions and trainee priority for training. Design/methodology/approach: – Participants who were experienced job incumbents responded to a survey related to foreign language usage, training, and policy. Findings: – When leaders showed support for training through their actions, trainees were more likely to perceive their leaders as placing a higher priority on training. Leader behaviors predicted trainee priority to train, because trainees believed their leaders set a higher priority for training. The leader behaviors that were important for trainees' priority to train were discretionary behaviors, not those leader behaviors mandated by the organization. Trainee perceptions of leader priority were more positively predictive of trainees' priority to train for trainees with less motivation to transfer of training. Originality/value: – Supervisor support is an important predictor of training outcomes. The authors expand this literature by focussing on the signals that leaders send to their subordinates regarding training priority. Leaders who exhibited discretionary behaviors in support of training appeared to create an environment in which trainees placed greater importance on training. Organizations need to be aware that mandating training activities might not be as important as encouraging leaders to place value on discretionary activities.